Variations of rhizosphere and bulk soil microbial community in successive planting of Chinese fir (Cunninghamia lanceolata) - Chen, Jiachen; Deng, Zhifang; Jiang, Zheng; Sun, Jin; Meng, Fangfang; Zuo, Xiaodong; Wu, Linkun; Cao, Guangqiu; Cao, Shijiang (Frontiers in Plant Science, 2022)
Successive planting and monoculture, as common forest management methods, are widely used globally, especially in Chinese fir plantations in the subtropical areas of southern China. Although soil fertility depletion and productivity decline caused by successive planting have been widely reported, the underlying mechanism is still ambiguous. In this study, the composition and diversity of soil microorganisms (rhizosphere and non-rhizosphere soils) in first-generation Chinese fir plantation (FCP), second-generation Chinese fir plantation (SCP), third-generation Chinese fir plantation (TCP), and broadleaf forests (Phoebe zhennan S. Lee et F. N. Wei, CK) were examined with high-throughput sequencing technology. Our findings revealed that the diversity and richness of bacterial and fungal communities were remarkably reduced in TCP than FCP and SCP, and were remarkably different between FCP and SCP. At the phylum level, the fungi with greatest relative abundance were Basidiomycota (5.74%–32.88%) and Ascomycota (57.63%–87.38%), while the bacteria with the greatest relative abundance were Acidobacteria (23.16%–31.17%) and Proteobacteria (24.71%–29.32%) for all treatments in both soil types. Additionally, the relative abundance of some pathogens (Penicillium and Burkholderia) was considerably higher in TCP than in FCP and SCP, suggesting that the presence of pathogens is an important factor in the deterioration of soil fertility. Moreover, changes in fungal and bacterial communities were predominantly driven by soil dissolved organic carbon (DOC), DOCN, NO3--N, microbial biomass carbon (MBC), and MBCN. Overall, the long-term monoculture of Chinese fir exacerbated the imbalance of soil microbial community within the forest and remarkably reduced soil microbial community diversity.